2021
DOI: 10.3390/ijms22105352
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment in Follicular Lymphoma: Its Pro-Malignancy Role with Therapeutic Potential

Abstract: In the follicular lymphoma (FL) microenvironment, CXCR5+ICOS+PD1+BCL6+ follicular helper T (Tfh) cells, which closely correlate with FL B cells in neoplastic follicles, play a major role in supporting FL. Interleukin-4 secreted by Tfh cells triggers the upregulation of the lymphocyte chemoattractant CXCL12 in stromal cell precursors, in particular by fibroblastic reticular cells (FRCs). In turn, mesenchymal fistromal cells (MSCs) can be committed to FRC differentiation in the bone marrow and lymph nodes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Then, we assessed the association between the cuproptosis risk score and immune cell abundance. The results showed that the risk score was positively correlated with activated and effector memory CD4 T cells, memory B cells, and follicular helper T cells but negatively correlated with activated NK and resting CD4 + memory T cells, both of which are known for their pivotal roles in the antitumor immune response 37 . Studies have reported that patients with high memory T-cell activation have shorter OS, whereas those with high memory T-cell quiescence have longer OS 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Then, we assessed the association between the cuproptosis risk score and immune cell abundance. The results showed that the risk score was positively correlated with activated and effector memory CD4 T cells, memory B cells, and follicular helper T cells but negatively correlated with activated NK and resting CD4 + memory T cells, both of which are known for their pivotal roles in the antitumor immune response 37 . Studies have reported that patients with high memory T-cell activation have shorter OS, whereas those with high memory T-cell quiescence have longer OS 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of infiltration of tumor immune cells also differed between the high- and low-risk groups. Compared to the high-risk group, resting CD4 + memory T cells and follicular helper T cells, both of which were well acknowledged to exert an important antitumor immune response ( Watanabe, 2021 ), infiltrated at higher levels in the low-risk group; whereas tumorigenesis-, angiogenesis- and immune suppressing-related cell types, such as M2 macrophages, monocytes, antigen-presenting cells, and dendritic cells ( Nahas et al, 2019 ; Fu and Song, 2021 ), showed higher infiltration levels in the high-risk group. Furthermore, this study also found that patients with high-risk scores showed a worse prognosis than those with low-risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Functional loss of TNFRSF14 is implicated in orchestrating the composition of the immune environment via the ligation of the B- and T-lymphocyte attenuator (BTLA) and regulating the expression of stroma-derived cytokines [ 42 ]. These genetic events may thus contribute to the dense infiltration of tumor-associated immune cells, as observed histologically in PCFBCL.…”
Section: Discussionmentioning
confidence: 99%